Development of an Ankle Exoskeleton: Design, Modeling, and Testing - Gani Sergazin; Assylbek Ozhiken; Nursultan Zhetenbayev; Kassymbek Ozhikenov; Gulzhamal Tursunbayeva; Yerkebulan Nurgizat; Arman Uzbekbayev; Abu-Alim Ayazbay (Sensors)
This research presents the results of conceptual design and modeling of an exoskeleton. It is intended for ankle joint rehabilitation in patients with musculoskeletal disorders. The exoskeleton design includes three screw actuators that smoothly control motion in the planes of dorsal and plantar flexion, inversion, and eversion. The results of the virtual tests performed on the exoskeleton device demonstrated a high degree of adaptability to varying loads and different phases of motion. Controlled torque fluctuations and linear motion provide the necessary support during different phases of rehabilitation, which has a positive impact on the patient’s recovery rate. The advantages of the design include material availability, ease of use, and flexibility in customization, making it an attractive option for use in both clinical and home settings. The study emphasizes the importance of developing affordable and accurate rehabilitation devices that can adapt to individual patient needs.